2020
DOI: 10.3892/ijmm.2020.4836
|View full text |Cite
|
Sign up to set email alerts
|

miR‑93‑5p regulates the occurrence and development of esophageal carcinoma epithelial cells by targeting TGFβR2

Abstract: Emerging studies have indicated that the dysregulation of microRNAs (miRNAs or miRs) plays a vital role in the development and metastasis of tumors. However, the role of miR-93-5p in esophageal carcinoma (Ec) has not been extensively reported. The present study thus focused on the role of miR-93-5p and its downstream target in the occurrence and development of EC. Firstly, miRNA expression profiles associated with Ec were accessed from the TcGA_EScA dataset and analyzed. Subsequently, the expression patterns o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…When we analyzed the gene expression of TGFBR2 , which is the target of rno-miR-291a-3p, contrary to what was expected, the expression of this mRNA was upregulated. However, it has been reported that TGFBR2 could be regulated by other miRNAs such as rno-miR-19a-3p or hsa-miR-93-5p which are located within the miR-17-92a cluster in chromosome 13 ( Mogilyansky & Rigoutsos, 2013 ; Zou et al, 2016 ; Cai et al, 2021 ). In fact, we found a downregulation in the expression of miR-93-5p.…”
Section: Discussionmentioning
confidence: 99%
“…When we analyzed the gene expression of TGFBR2 , which is the target of rno-miR-291a-3p, contrary to what was expected, the expression of this mRNA was upregulated. However, it has been reported that TGFBR2 could be regulated by other miRNAs such as rno-miR-19a-3p or hsa-miR-93-5p which are located within the miR-17-92a cluster in chromosome 13 ( Mogilyansky & Rigoutsos, 2013 ; Zou et al, 2016 ; Cai et al, 2021 ). In fact, we found a downregulation in the expression of miR-93-5p.…”
Section: Discussionmentioning
confidence: 99%
“… MicroRNAs targeting the pathways of Wnt/β-catenin, IL6/Stat3, and TGF-β in esophageal squamous cell carcinoma metastasis. In esophageal squamous cell carcinoma (ESCC), miRNAs serve as crucial effector to Wnt/β-catenin, IL-6/STAT3 and TGF-β signalings, which is consistently involved in cancer metastasis[ 9 , 12 , 14 , 23 , 27 , 28 , 33 , 44 , 59 , 61 , 70 , 73 , 78 , 80 , 81 , 83 , 85 , 86 , 88 - 91 , 93 - 95 , 109 , 111 , 113 , 114 , 116 , 118 , 119 , 142 - 144 , 151 , 156 , 161 , 164 , 165 , 169 , 174 , 178 , 181 , 189 , 193 , 195 , 200 , 201 , 204 , 209 , 211 , 215 , 219 , 227 , 229 , 235 , 238 , 253 , 263 , 270 , 273 , 284 - 287 , 289 , …”
Section: The Genetic Mechanism Of Mirnas On Escc Metastasismentioning
confidence: 99%
“…Increased expression of miRNA-93 has been seen in a wide variety of cancer types ( 157 ), with upregulation in oesophageal cancers ( 158 , 159 ) being associated with poor prognosis and decreased efficacy of radiotherapy ( 160 ). In vitro forced overexpression in oesophageal cell lines has been found to increase proliferation, migration and invasion ( 159 , 161 ) concomitant with a decrease in the direct targets of miRNA-93, transforming growth factor beta receptor 2 TGFβR2). ( 161 ) and disabled 2 (DAB2) ( 159 ).…”
Section: The Relationship Between Specific Micrornas and Pdcd4 Expres...mentioning
confidence: 99%
“…In vitro forced overexpression in oesophageal cell lines has been found to increase proliferation, migration and invasion ( 159 , 161 ) concomitant with a decrease in the direct targets of miRNA-93, transforming growth factor beta receptor 2 TGFβR2). ( 161 ) and disabled 2 (DAB2) ( 159 ). Similarly, this microRNA has been found to be upregulated in gastric cancer ( 162 , 163 ) and expression correlates with poor survival and metastatic disease ( 164 , 165 ), Transfection and overexpression of miRNA-93 in gastric cancer cell lines also promotes an increase in proliferation, migration, invasion and chemoresistance ( 166 , 167 ) and decreases the expression of the tumour suppressors AHNAK ( 167 , 168 ) and TIMP-2 ( 165 ).…”
Section: The Relationship Between Specific Micrornas and Pdcd4 Expres...mentioning
confidence: 99%